2022
DOI: 10.2105/ajph.2021.306561
|View full text |Cite
|
Sign up to set email alerts
|

Inequities in Drinking Water Quality Among Domestic Well Communities and Community Water Systems, California, 2011‒2019

Abstract: Objectives. To evaluate universal access to clean drinking water by characterizing relationships between community sociodemographics and water contaminants in California domestic well areas (DWAs) and community water systems (CWSs). Methods. We integrated domestic well locations, CWS service boundaries, residential parcels, building footprints, and 2013–2017 American Community Survey data to estimate sociodemographic characteristics for DWAs and CWSs statewide. We derived mean drinking and groundwater contami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
56
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 41 publications
(60 citation statements)
references
References 23 publications
0
56
0
Order By: Relevance
“…Producing high-resolution CA-POP grids for various demographic variables estimated in the 2020 census, including racial and ethnic subgroups, can serve as a resource for studies that seek to evaluate these communities. A precursor to the 2020 CA-POP grids developed by the authors, based on 2017 American Community Survey block group and 2010 block source zones, were employed by Casey et al ( 2021) [ 38 ] to assess social inequalities in residential proximity to large methane-emitting sites and in Pace et al ( 2022) [ 39 ] to estimate racial/ethnic inequalities in estimated drinking water concentrations of arsenic, nitrate, and hexavalent chromium from community water systems and areas of potentially high domestic well prevalence, demonstrating the utility of CA-POP for environmental equity studies. As more socio-demographic variables are released by future U.S. Census Bureau’s American Community Surveys from the U.S. Census Bureau, additional grids based on these block group-level values may be produced and uploaded to the public CA-POP repository (github.com/njdepsky/CA-POP).…”
Section: Introductionmentioning
confidence: 99%
“…Producing high-resolution CA-POP grids for various demographic variables estimated in the 2020 census, including racial and ethnic subgroups, can serve as a resource for studies that seek to evaluate these communities. A precursor to the 2020 CA-POP grids developed by the authors, based on 2017 American Community Survey block group and 2010 block source zones, were employed by Casey et al ( 2021) [ 38 ] to assess social inequalities in residential proximity to large methane-emitting sites and in Pace et al ( 2022) [ 39 ] to estimate racial/ethnic inequalities in estimated drinking water concentrations of arsenic, nitrate, and hexavalent chromium from community water systems and areas of potentially high domestic well prevalence, demonstrating the utility of CA-POP for environmental equity studies. As more socio-demographic variables are released by future U.S. Census Bureau’s American Community Surveys from the U.S. Census Bureau, additional grids based on these block group-level values may be produced and uploaded to the public CA-POP repository (github.com/njdepsky/CA-POP).…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, communities served by domestic wells often face significant water quality challenges compared to those served by community water systems (CWSs). It is estimated that 1.3 million Californians rely on private domestic wells [15], which commonly serve rural, agricultural, and socioeconomically disadvantaged communities [16]. A recent statewide environmental justice study in California found that mean arsenic, nitrate and hexavalent chromium levels exceeded their respective MCLs for a greater proportion of people who used a domestic well compared to those who used a community water system, and that poor water quality in domestic well areas disproportionately impacted Latinx and communities of color [15].…”
Section: Introductionmentioning
confidence: 99%
“…It is estimated that 1.3 million Californians rely on private domestic wells [15], which commonly serve rural, agricultural, and socioeconomically disadvantaged communities [16]. A recent statewide environmental justice study in California found that mean arsenic, nitrate and hexavalent chromium levels exceeded their respective MCLs for a greater proportion of people who used a domestic well compared to those who used a community water system, and that poor water quality in domestic well areas disproportionately impacted Latinx and communities of color [15]. As these contaminants pose cancer and non-cancer health risks [17], such groundwater contamination threats can contribute to cumulative exposures from multiple chemical stressors and disproportionate health burdens among the impacted communities [11,12,14].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…1 In the United States, exposure to arsenic contamination in drinking water disproportionately impacts small, groundwater-reliant communities and communities of color. 2 , 3 These inequities are driven by a combination of natural, built, and sociopolitical factors. 4 The United Nations calls upon states to especially safeguard the right to safe water for groups that may face difficulties exercising this right, such as incarcerated people.…”
Section: Introductionmentioning
confidence: 99%